Regulatory Interaction between the Cellular Restriction Factor IFI16 and Viral pp65 (pUL83) Modulates Viral Gene Expression and IFI16 Protein Stability - Biolatti, Matteo; Dell'Oste, Valentina; Pautasso, Sara; Von Einem, Jens; Marschall, Manfred; Plachter, Bodo; Gariglio, Marisa; De Andrea, Marco; Landolfo, Santo (Journal of Virology, 2016)
A key player in the intrinsic resistance against human cytomegalovirus (HCMV) is the interferon-?-inducible protein 16 (IFI16), which behaves as a viral DNA sensor in the first hours postinfection and as a repressor of viral gene transcription in the later stages. Previous studies on HCMV replication demonstrated that IFI16 binds to the viral protein kinase pUL97, undergoes phosphorylation, and relocalizes to the cytoplasm of infected cells. In this study, we demonstrate that the tegument protein pp65 (pUL83) recruits IFI16 to the promoter of the UL54 gene and downregulates viral replication, as shown by use of the HCMV mutant v65Stop, which lacks pp65 expression. Interestingly, at late time points of HCMV infection, IFI16 is stabilized by its interaction with pp65, which stood in contrast to IFI16 degradation, observed in herpes simplex virus 1 (HSV-1)-infected cells. Moreover, we found that its translocation to the cytoplasm, in addition to pUL97, strictly depends on pp65, as demonstrated with the HCMV mutant RV-VM1, which expresses a form of pp65 unable to translocate into the cytoplasm. Thus, these data reveal a dual role for pp65: during early infection, it modulates IFI16 activity at the promoter of immediate-early and early genes; subsequently, it delocalizes IFI16 from the nucleus into the cytoplasm, thereby stabilizing and protecting it from degradation. Overall, these data identify a novel activity of the pp65/IFI16 interactome involved in the regulation of UL54 gene expression and IFI16 stability during early and late phases of HCMV replication.The DNA sensor IFI16, a member of the PYHIN proteins, restricts HCMV replication by impairing viral DNA synthesis. Using a mutant virus lacking the tegument protein pp65 (v65Stop), we demonstrate that pp65 recruits IFI16 to the early UL54 gene promoter. As a putative counteraction to its restriction activity, pp65 supports the nucleocytoplasmic export of IFI16, which was demonstrated with the viral mutant RV-VM1 expressing a nuclearly retained pp65. These data reveal a dual role of pp65 in IFI16 regulation: in the early phase of HCMV infection, it contributes to viral evasion from IFI16 restriction activity, while at later time points, it promotes the nuclear delocalization of IFI16, thereby stabilizing and protecting it from degradation. In the present work, we further clarify the mechanisms HCMV relies on to overcome intracellular innate immune restriction and provide new insights into the relevance of DNA-sensing restriction factor IFI16 during HCMV infection.
EVALuna2:8328